Anti-Neuronal Nuclear Antibody 3 Autoimmunity Targets Dachshund Homolog 1. (5th December 2022) - Zekeridou, Anastasia; Yang, Binxia; Lennon, Vanda; Yong, Guo; Wu, Liang; Lucchinetti, Claudia; McKeon, Andrew; Pittock, Sean; Flanagan, Eoin
Abstract : Objective: To identify the autoantigen defined by Anti-Neuronal Nuclear Antibody-type 3 (ANNA3)-IgG and describe the clinical phenotype of seropositive patients. Background: ANNA3 was described in 11 patients with multifocal neurological presentations and cancer; its detection is based on the characteristic immunofluorescence staining on mouse tissue sections; ignorance of the antigen's molecular identity has precluded its ready detection in clinical practice. Design/Methods: This study was performed at the Mayo Clinic Neuroimmunology Laboratory. The ANNA3-IgG antigen, identified by immunoprecipitation and mass spectrometry as Dachshund-homolog 1 (DACH1), was confirmed by using a commercial DACH1-specific IgG for immunohistochemical colocalization, antigen-specific Western blot, transfected cell-based immunofluorescence, and immune absorption experiments. Clinical data were abstracted from patients' medical records or provided by referring physicians. Results: IgG in 32 ANNA3 seropositive patient sera, but in none of 145 controls, bound to DACH1. Clinical information was available for 30 patients (median age, 63.5 years [range, 49-88]; 67% female). Neurological manifestations included neuropathy, 12; cognitive difficulties or encephalitis, 11; ataxia, 8; dysautonomia, 7 (two additionally had diarrhea and esophageal spasm); chorioretinopathy, 1. Clinical improvement was noted in 8 of 11, all treated with immunosuppressants or oncologic treatment. In two patients, the neurological syndrome appeared or worsened during immune checkpoint inhibitor cancer immunotherapy. A neoplasm was found in 27 patients (90%); fourteen were of neuroendocrine lineage. Coexisting neural autoantibodies were detected in 14 patients (47%), and most predicted a neuroendocrine tumor (specific for neuronal intermediate filaments, collapsin response-mediator protein-5, voltage-gated calcium channel [P/Q-type], ANNA1, SOX1, Purkinje-cell cytoplasmic autoantibody type 2/microtubule-associated-protein-1B). Conclusions: IgG specific for DACH1 is a serological biomarker of neurological autoimmunity and cancer in patients of middle-age or older. DACH1-IgG is a valuable addition to comprehensive autoimmune and paraneoplastic neural antibody evaluations in clinical practice.